Tradition and modernity in cartoons from Quesada and Davila for “Faro de Vigo” - Caballero Wangüemert, Félix (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Fernando Quesada (1933-2006) and Luís Davila (1972) are two of the main humorists in the history of the Spanish newspaper “Faro de Vigo”. Quesada collaborated on it between 1961 and 2011, and Davila has collaborated since 1996. Both have in common the great popularity and comicalness of their cartoons and the clash between tradition and modernity as the cause of that comilcaness. This communication tries to discover the keys to this clash, using qualitative content analysis from 30 cartoons from each humorist selected from the anthologies “Chispas de Quesada” (2007) and “O Bichero. 20 years” (2019).